Hydroxysafflor Yellow A Attenuates the Apoptosis of Peripheral Blood CD4+ T Lymphocytes in a Murine Model of Sepsis - Wang, Jinping; Wang, Ping; Gui, Shuiqing; Li, Yun; Chen, Runhua; Zeng, Renqing; Zhao, Peiyan; Wu, Hanwei; Huang, Zheyu; Wu, Jianlong (Frontiers in Pharmacology, 2017)
Sepsis is generally viewed as a condition of overwhelming inflammation, leading to lymphocyte apoptosis and multiple organ dysfunctions. Hydroxysafflor Yellow A (HSYA) exerts anti-inflammatory and anti-apoptotic actions in infectious diseases. However, its therapeutic effect of HSYA on polymicrobial sepsis remains unknown. This study investigated the therapeutic effect and the mechanisms of action of HSYA on immunosuppression in murine sepsis induced by cecal ligation and puncture(CLP).NIH mice were randomly divided into four groups (control group,shamgroup,CLP group and CLP +HSYA group). HSYA (120 mg/kg) was intravenously injected at 12h before the operation, 0h and 12 h after CLP. Blood inflammatory cytokines, CD4+ and CD8+T lymphocytes apoptosis, the levels of Cytc, Bax, Bcl-2, caspase-9, and caspase-3 were examined. CLP significantly elevated plasma levels of IL-6 、 IL-10 and TNF-alpha and induced CD4+lymphocytes apoptosis in murine compared to control and sham groups. These changes were accompanied by increases of pro-apoptotic proteins Cytc, Bax, caspase-9, and caspase-3 and downregulation of anti-apoptotic protein Bcl-2 in CD4+lymphocytes of CLP-treated murine. Unlike CD4+T cells, CD8+ T cells did not show enhanced apoptosis in CLP-treated group compared to other groups. Of note, HSYA treatment inhibited all above changes observed in CD4+T cells, and significantly increased the ratio of CD4+:CD8+ in CLP-treated murine. HSYA was effective in protecting CD4+ lymphocytes under sepsis conditions and this protection may be attributed to its anti-inflammatory and anti-apoptotic actions.